(untitled) (Zaporizhzhia Historical Review, 2021)
Basing upon the accessible sources, the author investigates the question of political orientation of the starshyna (higher officers) of Poltava regiment during significant events of 1708-1709. He concludes that Poltava regiment supported Hetman Mazepa’s course. He also defines the division of Poltava regimental and company officers into three groups: followers, potential followers and opponents of the Hetman.